2019
DOI: 10.1093/jn/nxz041
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxyvitamin D Concentrations Are Inversely Associated with All-Cause Mortality among a Prospective Cohort of Chinese Adults Aged ≥80 Years

Abstract: Background High concentrations of plasma 25-hydroxyvitamin D [25(OH)D], a marker of circulating vitamin D, have been associated with a lower risk of mortality in epidemiologic studies of multiple populations, but the association for Chinese adults aged ≥80 y (oldest old) remains unclear. Objective We investigated the association between plasma [25(OH)D] concentration and all-cause mortality among Chinese adults aged ≥80 y. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A Mendelian randomization study reported that variations of SNPs that reduce serum 25(OH)D concentration accounted for a 20% increase in all-cause mortality rate per each 8 ng/mL decrease in serum 25(OH)D [118]. A prospective study of Chinese adults aged >80 years (median age, 93 years) with mean baseline 25(OH)D of 14 ng/mL followed up for 5466 person-years reported that participants with the highest 25(OH)D concentrations had a 39% reduced mortality rate [119]. In support of those data, a 20-year follow-up study in Sweden reported that sun avoidance was associated with a reduced life expectancy of 0.6 to 2.1 years compared with the highest sun exposure [120].…”
Section: Resultsmentioning
confidence: 99%
“…A Mendelian randomization study reported that variations of SNPs that reduce serum 25(OH)D concentration accounted for a 20% increase in all-cause mortality rate per each 8 ng/mL decrease in serum 25(OH)D [118]. A prospective study of Chinese adults aged >80 years (median age, 93 years) with mean baseline 25(OH)D of 14 ng/mL followed up for 5466 person-years reported that participants with the highest 25(OH)D concentrations had a 39% reduced mortality rate [119]. In support of those data, a 20-year follow-up study in Sweden reported that sun avoidance was associated with a reduced life expectancy of 0.6 to 2.1 years compared with the highest sun exposure [120].…”
Section: Resultsmentioning
confidence: 99%
“…The association of 25(OH)D with all-cause mortality has been extensively examined in community-based individuals aged > 80 years. Several studies have found a significant association (HR 1.56–2.02) [ 10 , 11 , 12 , 13 ], while others have reported a negative association [ 14 , 15 , 16 , 17 ]. However, to date, the association between 25(OH)D and all-cause mortality has not been investigated in centenarians.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults frequently have serum 25(OH)D insufficiency [ 9 ]. The association between 25(OH)D and all-cause mortality in community-based individuals aged > 80 years remains uncertain, with several studies finding significant associations [ 10 , 11 , 12 , 13 ] and others reporting negative results [ 14 , 15 , 16 , 17 ]. The association between 25(OH)D and all-cause mortality has not been investigated in centenarians.…”
Section: Introductionmentioning
confidence: 99%
“…A similar analysis has been reported for the Chinese Longitudial Health and Longevity Study (CLHLS). In that study, Mao et al looked at plasma 25(OH)D levels in 2185 Chinese adults older than 79 years (mean 93 yrs) (32). There, all-cause mortality decreased progressively with rising plasma 25(OH)D, with the lowest mortality in those with 25(OH)D at or higher than 75 nmol/l (30 ng/ml).…”
Section: Mortalitymentioning
confidence: 99%